Knowledge, attitudes, and practices of family physicians and nurses regarding unintentional injuries among children under 15 years in Cairo, Egypt. Issue 1 (2nd January 2017) - Elboray, Shereen; Elawdy, Mohamed Yehia; Dewedar, Sahar; Elezz, Nahla Abo; El-Setouhy, Maged; Smith, Gordon S.; Hirshon, Jon Mark
Abstract : Unintentional injuries are a leading cause of death among children, especially in developing countries. Lack of reliable data regarding primary health care professionals' role in childhood unintentional injury prevention hinders the development of effective prevention strategies. A survey of 99 family physicians and nurses from 10 family health centres sought to develop insight into their knowledge, attitudes, and practices regarding unintentional injury prevention for children <15 in Cairo, Egypt. Approximately, 60% were familiar with the terms unintentional injuries and injury prevention . Falls and road traffic crashes were identified as primary causes of childhood injuries by 54.5%. While >90% agreed injury prevention counselling (IPC) could be effective, only 50.5% provided IPC. Lack of time and educational materials were the leading barriers to provision of IPC (91.9% and 85.9%, respectively), while thinking counselling is not part of their clinical duties was the least perceived barrier (9.1%). There is a large disconnect between providers' knowledge, attitudes and practices regarding IPC, more training and provision of counselling tools are essential for improving IPC by Egyptian medical providers.